Lipid nanoparticles for nasal/intranasal drug delivery - Cunha, S. (2021)
Studies on the development of drug delivery systems have increased because these systems have particular characteristics that allow them to improve therapeutics. Among these, lipid nanoparticles (solid lipid nanoparticles, SLNs; and nanostructured lipid carriers, NLCs) have demonstrated suitability for drug targeting. The nasal administration of drug-loaded lipid nanoparticles showed effectiveness in treating central nervous system (CNS) disorders, particularly neurodegenerative diseases, because the nasal route (also called intranasal route) allows direct nose-to-brain drug delivery by means of lipid nanoparticles. Nonetheless, the feasibility of this application remains an open field for researchers. Drawbacks must be overcome before reaching the clinic (e.g., drug absorption at subtherapeutic levels, rapid mucociliary clearance). The intranasal administration of drugs for systemic absorption is effective for treating other conditions, such as cardiovascular diseases, infections, severe pain, and menopausal syndrome. In the near future, it is expected that patients will benefit from the advantages of lipid nanoparticle-based formulations, via the nasal/intranasal route, which bypasses the blood-brain barrier (BBB), avoiding first-pass metabolism and gastrointestinal degradation. This review discusses the use of SLNs and NLCs for nasal drug administration. A brief description of the nasal route and the features of SLNs and NLCs is initially provided.